A pharmacist-led opioid de-escalation program after completion of chemoradiotherapy in locally advanced head and neck cancer - Horinouchi, Ai; Enokida, Tomohiro; Suzuki, Shinya; Kamata, Hayato; Kaneko, Asumi; Matsuyama, Chihiro; Fujisawa, Takao; Ueda, Yuri; Ito, Kazue; Okano, Susumu; Kawasaki, Toshikatsu; Tahara, Makoto (Frontiers in Oncology, 2023)
Background: Persistent opioid use frequently leads to substantial negative impacts on quality of life, and as the outlook for numerous cancer types continues to improve, these complications become increasingly crucial. It is essential to acknowledge that extended or excessive opioid use may result in adverse effects in patients who completed radiation therapy (RT).: In this time-series analysis, we compared the outcomes of patients who participated in the pharmacist-led opioid de-escalation (PLODE) program after completing concurrent radiotherapy (CRT) between June 2018 and February 2019 against patients who completed CRT between June 2017 and March 2018 and did not participate in the program. Results: Among 61 patients, 16 (26%) used opioids after completing CRT and participated in the PLODE program. Before starting the program, 93 patients completed CRT between June 2017 and March 2018 and 32 (34%) used opioids at CRT completion. These patients were deemed the control group. In the PLODE group, outpatient pharmacist intervention was performed, with 29 total interventions related to opioid use, of which 16 (55%) recommended tapering or discontinuing opioids according to the definition of this program. Patients who participated in the PLODE program discontinued opioids significantly earlier than those in the control group (median time to opioid discontinuation 11 days vs. 24.5 days, p < 0.001). None of the patients in the PLODE group resumed opioid use following discontinuation or escalated opioid dosing due to worsening pain. Conclusion: This study showed the utility of pharmacist-initiated interventions for opioid use in patients with head and neck cancer who had completed CRT.